Monocyte to high-density lipoprotein cholesterol ratio as long-term prognostic marker in patients with coronary artery disease undergoing percutaneous coronary intervention - Ting-Ting Wu (Lipids in Health and Disease, 2019)
Abstract Background The relation between monocyte to high-density lipoprotein cholesterol ratio (MHR) and coronary artery disease (CAD) undergoing percutaneous coronary intervention (PCI) remains controversial. The present study aims to assess the prognostic value of MHR in patients with CAD who underwent PCI. Methods A total of 673 CAD patients were retrospectively enrolled and divided into four groups according to MHR values. Multivariate Cox regression analysis was performed to study the effects of different variables to clinical outcomes reported as major adverse cardiac events (MACE) and all-cause mortality (ACM). Results In a multivariate Cox analysis, after adjustment of other confounders, MHR was found to be an independent predictor of ACM (HR: 3.655; 95% CI: 1.170–11.419, P = 0.026) and MACE (HR =2.390, 95% CI 1.379–4.143, p < 0.002). Having a MHR in the third and fourth quartile were associated with a 2.83-fold and 3.26 -flod increased risk of MACE. Conclusions MHR is an independent predictor of ACM and MACE in CAD patients undergoing PCI.